Augmented Post-Induction Therapy for Children with High-Risk Acute Lymphoblastic Leukemia and a Slow Response to Initial Therapy - Rahman, ATMA; Gupta, SK; Mannan, MA; Nahar, K (Kathmandu University Medical Journal, 2014)
Background Children with high-risk acute lymphoblastic leukemia (ALL) who have a slow response to initial chemotherapy (more than 25 percent blasts in the bone marrow on day 7) have a poor outcome despite intensive therapy. We conducted a randomized trial in which such patients were treated with either an augmented intensive regimen of post-induction chemotherapy or a standard regimen of intensive post-induction chemotherapy. Objective To compare the effect of augmented therapy with standard intensive post induction therapy in children with high-risk ALL who entered remission after a slow response to initial therapy. Methods Between January 2005 and December 2011, 311 children with newly diagnosed ALL who were either 1 to 9 years of age with white cell counts of at least 50,000 per cubic millimeter or 10 years of age or older, had a slow response to initial therapy, and entered remission at the end of induction chemotherapy were randomly assigned to receive standard therapy (156 children) or augmented therapy (155). Those with lymphomatous features were excluded. Event-free survival and overall survival were assessed from the end of induction treatment. Results The outcome at five years was significantly better in the augmented-therapy group than in the standard-therapy group. The difference between treatments was most pronounced among patients one to nine years of age, all of whom had white-cell counts of at least 50,000 per cubic millimeter (P<0.001). Risk factors for an adverse event in the entire cohort included a white-cell count of 200,000 per cubic millimeter or higher (P=0.004). The toxic effects of augmented therapy were considerable but manageable. Conclusion Augmented post-induction chemotherapy results in an excellent outcome for most patients with high-risk ALL and a slow response to initial therapy. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10996 Kathmandu Univ Med J 2012;10(4):53-59